Effect of Vitafert on the digestive use of nitrogen in roosters that consume Moringa oleifera forage meal. Technical note - Bustamante, Daymara; Savón, Lourdes; Elías, A.; Caro, Y.; Sierra, F.; Almeida, M. (Cuban Journal of Agricultural Science, 2016)
A total of 16 colostomized roosters (hybrid H5) were used, housed in metabolic cages, to evaluate the effect of dry Vitafert on the digestive use of nitrogen (N) of moringa forage meal. The treatments were: I) control diet, II) 10 % of moringa forage meal, III) 2 % of dry Vitafertand IV) mixture of 10% of moringa forage meal with 2 % of dry Vitafert. A completely randomized design with four repetitions / treatment was used. The dry Vitafert was prepared from the mixtureof liquid Vitafert with corn-meal (1:1). The chemical composition and nitrogen use was determined. The N intake (g/d) and fecal digestibility of N (%) in the animals, which consumed the mixtureof moringa forage meal with dry Vitafert, was higher (P ˂ 0.001) compared to those who intake moringa forage meal. Fecal excretion of N (g/d) did not differ between treatments. It is concluded that the inclusion of dry Vitafert could stimulate the digestive use of N in roosters fed moringa forage meal.Key words: Vitafert, moringa, roosters, fecal digestibility of nitrogen